A Synthesis of Sustainable Public Transportation Logistics Model - Chutikorntaweesin, Ornpapha; Yodthong, Thuchaphon (International Journal of Scientific Research and Management (IJSRM), 2022)
The purpose of this research was to synthesize the sustainable public transportation logistics model. The researchers reviewed the related literature in the 5 years prior to the COVID-19 pandemic. The research process began with searching, reviewing, analyzing, synthesizing and summarizing the data. The results showed that the key components of the sustainable public transportation logistics model consisted of 3 components:• Corporate of Governance: it included 1) Urban Form which were (1) Physical Form and Land Use, (2) Land Area and Density, (3) Centralities and Regionalism; and 2) Transport Policy which were (1) Regional Integration, (2) Funding and Finances.• Logistics Management: it included 1) Physical Flow which were (1) The Speed of Transportation, (2) The Economies of Transportation, (3) The Safety of Transportation, (4) Quantity of Vehicles in Transportation, (5) The Convenience of Transportation, (6) The Certainty and Timeliness in Transportation; 2) Information Flow which were (1) Internal Communication, (2) External Communication; and 3) Financial Flow which were (1) Determine the Appropriate Fare, (2) Smart Card, (3) Common Ticketing System.• Sustainable Public Transportation: it included 1) Economic Dimension which were (1) Funding, (2) Demand Management; 2) Social Dimension which were (1) Differences in Spatial Distribution, (2) Travel Expenses, (3) Health, (4) Public Safety; and 3) Environmental Dimension which were (1) Greenhouse Gas Emission, (2) Fossil Fuel, (3) Renewable Energy.